“It’s just a joke”: gender, sexuality and trivialisation in adolescent online violence such as cyberhate, cyberbullying, and online grooming - María Reneses; María Riberas-Gutiérrez; Nereida Bueno-Guerra (Humanities & Social Sciences Communications)
Abstract The article presents the results of part of the research conducted for the European Union Horizon 2020 project RAYUELA on cybercrime and minors, analysed from a gender perspective. Using a qualitative approach in eight preliminary discussion groups with adolescents in different European countries (Estonia, Spain, Portugal, Greece, and Slovakia), and a second phase of further investigation through quantitative analysis of a representative survey in Madrid (N = 682) and Estonia (N = 415), we expose the gender differences both in victimisation (higher in girls and non-heterosexual youth) and in aggression (higher in boys) related to different forms of online violence including cyberbullying, hate speech, and online grooming. These differences can be understood as forms of violence that are sustained while promoting gender normativity. We discuss three conclusions: 1. Online violence as a practice that reinforces gender roles; 2. The trivialisation of symbolic violence through humour and consequent victim blaming; and 3. The effects that differential discourse on risk can have on the construction of sexuality.